Towards a knowledge-based organizational culture – discussion on empirical studies - Pietruszka-Ortyl, Anna (Management and Administration Journal, 2019)
The starting point of this paper is characteristic of the essence of organizational pathologies and dysfunctions. This discussion is a contribution of deliberation on the development of an optimal organizational culture - permitting the acquisition and maintenance of key employees. The present publication presents the results of empirical research regarding dysfunction and the pathology of the organizational culture of enterprises in Poland. 195 respondents were examined whose opinions were interpreted in the context of the challenges of creating a model, in terms of the knowledge economy, types of organizational culture - a culture based on knowledge, a culture of trust and a culture of cooperation.